Domain Diri dalam Adab Guru Menurut Imam Abū Ḥanīfah (Kajian Ke Arah Membentuk Etika Profesion Perguruan Islam) - Mamat, Mohd Anuar; Ibrahim, Muhammad Lukman; Sa’ari, Che Zarrina; Syed Abdul Rahman, Syed Mohammad Hilmi; Ismail, Zawawi; Wan Abdullah, Wan Suhaimi; Jusoh,, Che’Razi (2018)
The rules of conduct for teachers is one of the important elements in Islamic education. It is closely associated with the effort to the realization of a quality education and an effective teaching. This article presents the personal domain in this topic as elaborated by Imam Abū Ḥanīfah in his educational treatises, namely al-‘Ālim wa al-Muta‘allim, Waṣiyyah Abī Ḥanīfah li Abī Yūsuf, Waṣiyyah Abū Ḥanīfah li Ibnihi Ḥammād, and Waṣiyyah Abū Ḥanīfah ilā Tilmīdhihi Yūsuf bin Khālid al-Samtī al-Baṣrī. The authors found that there are seven elements in personal domain suggested by Abū Ḥanīfah in his educational treatises. These elements namely, sincerely in learning and teaching; pay attention in improving the deeds of taqwa, worship, fasting and reciting al-Quran; plan wisely in managing time, avoiding less important matters, optimizing learning, and self-esteem; being aware of God’s attention, feeling the sufficiency of His gift, living in khauf (fear) and rajā ‘(hopefully) and kind thoughts about Him; keeping dignity and acting as a teacher by doing good things and be modest in every business; avoid bad and vain actions and always be enthusiastic in performing a job as a teacher. These elements are very important in teachers’ profession. This study is also intended to reveal this topic based on Islamic scholar thought in order to formulate the professional code of ethics for Islamic teachers and to solve ethical problems nowadays.